(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article explains some topics on the use of STEAM technologies in mathematics, introduction to mathematics through the STEAM approach and applications of mathematics to various fields. It discusses the advantages of mathematics over other disciplines.